A comparative scanning electron microscopy study between hand instrument, ultrasonic scaling and erbium doped:Yttirum aluminum garnet laser on root surface: A morphological and thermal analysis - Mitul Kumar Mishra; Shobha Prakash (Wolters Kluwer Medknow Publications, 2013)
Background and Objectives: Scaling and root planing is one of the most commonly used procedures for the treatment of periodontal diseases. Removal of calculus using conventional hand instruments is incomplete and rather time consuming. In search of more efficient and less difficult instrumentation, investigators have proposed lasers as an alternative or as adjuncts to scaling and root planing. Hence, the purpose of the present study was to evaluate the effectiveness of erbium doped: Yttirum aluminum garnet (Er:YAG) laser scaling and root planing alone or as an adjunct to hand and ultrasonic instrumentation. Subjects and Methods: A total of 75 freshly extracted periodontally involved single rooted teeth were collected. Teeth were randomly divided into five treatment groups having 15 teeth each: Hand scaling only, ultrasonic scaling only, Er:YAG laser scaling only, hand scaling + Er:YAG laser scaling and ultrasonic scaling + Er:YAG laser scaling. Specimens were subjected to scanning electron microscopy and photographs were evaluated by three examiners who were blinded to the study. Parameters included were remaining calculus index, loss of tooth substance index, roughness loss of tooth substance index, presence or absence of smear layer, thermal damage and any other morphological damage. Results: Er:YAG laser treated specimens showed similar effectiveness in calculus removal to the other test groups whereas tooth substance loss and tooth surface roughness was more on comparison with other groups. Ultrasonic treated specimens showed better results as compared to other groups with different parameters. However, smear layer presence was seen more with hand and ultrasonic groups. Very few laser treated specimens showed thermal damage and morphological change. Interpretation and Conclusion: In our study, ultrasonic scaling specimen have shown root surface clean and practically unaltered. On the other hand, hand instrument have produced a plane surface, but removed more tooth structure. The laser treated specimens showed rough surfaces without much residual deposit or any other sign of morphological change.